Fractures of the Mandibular Condyle - Vincent, Aurora G.; Ducic, Yadranko; Kellman, Robert (Facial Plastic Surgery, 2019)
There exists no consensus “gold standard” treatment for condylar fractures, and there is continued debate on whether condylar fractures should undergo surgical or conservative management. Herein, we review various techniques of conservative, closed, and open surgical treatments of condylar fractures. Also, we review complications associated with each treatment modality and compare and contrast closed and open management. Standardization of fracture classification schemes and treatment modalities is needed to elucidate the best course of action for each patient and each fracture.
Keywords: mandible fracture; subcondylar fractures; condylar head fractures; surgical approaches